Effects of 3D-multiple object tracking on reaction time performance in high-performance varsity swimmers - Snowden, T. M.; Hogan, K. C.; Sparks, T. J.; Stein, R. G.; Lysenko-Martin, M. R.; Christie, B. R. (Journal of Athletic Enhancement, 2020)
Elite swimming is highly competitive; first place is often determined by only milliseconds. Improving off-the-block reaction time may serve as means to improve overall performance. The current study sought to determine whether repeated three-dimensional multiple object tracking training improves reaction times to auditory cues in high-performance varsity swimmers. Experimental participants (n=15; ages 18-25) were initially assessed for off-the block reaction times, as well as visual reaction times. Experimental participants then completed ten training sessions of three-dimensional multiple object tracking over a five-week period, after which off-the-block and visual reaction times were re-evaluated. Off-the-block reaction times improved in both the experimental and control groups (Ex: W=120, p=0.00072; Con: W=45, p=0.0039), however the improvement observed in the experimental group was significantly greater than that observed in the control group (W=10, p=0.00059). The experimental group also showed significant improvements in the ruler task, a measure of visual reaction time for both their right hand (W=111, p=0.0020) and left hand (W=113, p=0.0012). To our knowledge, this is the first evidence that training visual selective attention can positively affect auditory selective attention in nonvisually dominated sports.